The Relation of the Role of Financial Intermediaries in Capital Markets and Sustainable Development - Kushev, Anton (Research Papers, 2025)
The economic crises as well as the pandemics worldwide show that a change in thinking is needed regarding the use of resources as well as relationships in society. In this context, the issue of sustainable development is fundamental to human development. Therefore, establishing the relationship between sustainable development and the factors having a positive or negative impact on it, with an accent on the capital market, is essential.
Keywords: Sustainable development; Relation; Financial intermediaries; Fintech; Capital markets